VIOLATIONS OF MAXIMS ANALYSIS OF COOPERATIVE PRINCIPLE IN MALEFICENT MOVIE - Maria Anggryani Eno Toda; Imam Ghozali (JELLT (Journal of English Language and Language Teaching), 2017)
The objectives of this research are (1) to describe patterns of maxims violation made by the characters, and (2) to find out reasons why the characters violate the maxims in â€˜â€™Maleficentâ€ movie. This research belongs to a discourse study. The data for this study are 25 dialogues uttered by the characters and uses Griceâ€™s theory of cooperative principle and its maxims to describe the utterances and patterns of the violation of the maxims. The researchers also use Goffmanâ€™s theory, Christoffersenâ€™ theory and Khosravizadeh and Sadehvandiâ€™s idea to analyze the reasons why the characters violate the maxims. The findings show that there are two patterns of maxims violations namely violation one maxim and more than one maxims. In addition, there are seven reasons used by the characters to violate the maxims. The most frequent reason is hiding the truth (20 times), followed by saving face (15), avoiding discussion (5 times), expressing feelings (4 times), pleasing the hearer (3 times), avoiding punishment (2), and the last is building someoneâ€™s belief (1 time).